2021
DOI: 10.1029/2021ea001670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Candidate Landing Region for Tianwen‐1—China's First Mission to Mars

Abstract: This paper presents our efforts to characterize the candidate landing region (109°–133°E, 23°–30°N) for Tianwen‐1, China's first mission to Mars, in terms of engineering safety and scientific significance. Topographic analysis reveals that the region has a low elevation around −4,230 m, and 98% of the region have slopes smaller than 8°. The geomorphological mapping and analysis show that the region has an average crater density of about 28 craters (≥200 m in diameter) per 100 square kilometers, with several cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The geometric accuracies of the generated image mosaic and DEM were evaluated by comparison with reference data. Mars Reconnaissance Orbiter (MRO) Context Camera (CTX) images were used to generate an image mosaic (6 m/pixel) covering the same area (Wu et al., 2021). The CTX images were map‐projected based on the Mars Orbiter Laser Altimeter (MOLA) DEM and mosaicked by using our in‐house photogrammetric software (Hu & Wu, 2019).…”
Section: Landing Site Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The geometric accuracies of the generated image mosaic and DEM were evaluated by comparison with reference data. Mars Reconnaissance Orbiter (MRO) Context Camera (CTX) images were used to generate an image mosaic (6 m/pixel) covering the same area (Wu et al., 2021). The CTX images were map‐projected based on the Mars Orbiter Laser Altimeter (MOLA) DEM and mosaicked by using our in‐house photogrammetric software (Hu & Wu, 2019).…”
Section: Landing Site Selectionmentioning
confidence: 99%
“…The landing area of Tianwen‐1 (Zhurong rover) was mapped as a Late Hesperian lowland (lHl) unit (Tanaka et al., 2014) with an estimated age of 3.34 Ga (Wu et al., 2021). Previous studies have indicated that the lHl unit is mainly composed of Vastitas Borealis Formation (VBF) materials, which might have originated from fluvial, lacustrine or marine sediments (Carr & Head, 2019; Ivanov & Hiesinger, 2020; Kreslavsky & Head, 2002).…”
Section: Landing Site Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is composed of an orbiter, a lander, and a rover. Given the rover's requirement for touchdown safety and mobility, two candidate landing areas were selected for the Mars exploration mission in the latitude range of 5-30°N (Ye et al, 2017;B. Wu, Dong, et al, 2021): the southern Utopia-Isidis Planitia (SUIP) and southern Chryse Planitia (SCP; Figure 2).…”
Section: Tianwen-1 Missionmentioning
confidence: 99%